Manajemen Keuangan Madrasah yang Bersumber dari Masyarakat - Khoirul Anam (AT-TURATS, 2019)
Indicator of Indonesian’s national development is the quality of education. Islamic school’s funding is an important instrument to improve access, quality, and competitiveness of educational institution. Islamic schools education funding source are joint responsibility of the government and the community. Community-sources funding is managed by the Islamic school committee and supervised by the internal supervisor. Moreover, the financial management was carried out with the following mechanism: submitting the proposal from the Islamic school to the committee, approving the proposal, disbursement process, and then reporting the agenda to the Islamic school committee. Therefore, the committee’s internal supervisor is controlled every 6 months. In addition, the following barriers come from the parents and student.